Mutually exclusive or joint scheme? Effectiveness of mandatory and voluntary training in enhancing employee performance - Ilham Safar; Hari Yeni; Novita Kumala Sari; Shalahuddin Shalahuddin; Muh. Asdar (Faculty of Economics and Business, University of Muhammadiyah Malang, 2026)
Employee training is widely recognized as a key mechanism for enhancing individual capabilities and organizational performance. The literature commonly distinguishes between mandatory training, which emphasizes compliance and standardization, and voluntary training, which is driven by employee autonomy and self-directed learning. However, empirical findings remain fragmented, and limited research has systematically examined how these training approaches are jointly positioned within the broader literature. This study employs a systematic literature synthesis with a descriptive mapping approach to analyze patterns in how mandatory and voluntary training are associated with employee and organizational performance. A total of 305 peer-reviewed abstracts published between 2013 and 2023 were retrieved from Scopus-indexed journals and analyzed to identify recurring themes and reported associations across diverse organizational contexts. The findings show that both training types are frequently linked to performance-related outcomes, with mandatory training primarily associated with compliance and operational consistency, and voluntary training more commonly linked to motivation, engagement, innovation, and long-term professional development. Importantly, many studies emphasize the complementary role of mandatory and voluntary training, suggesting that training effectiveness is often discussed within an integrated rather than a mutually exclusive framework. This synthesis underscores the relevance of hybrid training systems that combine compliance-oriented and employee-driven learning to support adaptive and sustainable organizational development.